Economics of satellite campuses - Catherine Roween C. Almaden (Philippine Institute for Development Studies (PIDS), 2024)
This research provides a comprehensive comparison of the financial, educational, and socio-spatial considerations in establishing State Universities and Colleges (SUCs) satellite campuses versus enhancing support mechanisms for existing SUCs in the Philippines. It highlights their critical role in expanding access to higher education, particularly for underserved and geographically isolated communities. Building on literature that identifies satellite campuses as tools for addressing educational disparities and fostering regional socio-economic development, the study emphasizes cost-effectiveness in decision-making. Using a mixed-methods approach, it combines quantitative cost-effectiveness analysis with qualitative insights from Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) with SUC stakeholders to explore financial and operational challenges. The cost-effectiveness analysis utilizes key financial metrics such as Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR). Findings indicate that while satellite campuses offer opportunities to improve educational access, their financial sustainability is constrained by high initial investments and operational costs. Current low-fee structures in SUCs limit revenue generation, with long-term projections rarely covering infrastructure and operational expenses. Revenue-enhancing strategies are essential to address these constraints and ensure viability. Infrastructure development emerges as a major cost factor, with many SUCs relying on partnerships with Local Government Units (LGUs) for land donations. However, budget limitations remain a significant barrier. Qualitative data highlight the socio-economic benefits of satellite campuses, including empowerment of marginalized populations and local economic growth. Aligning educational programs with local needs is identified as key to maximizing impact. Enrollment trends reveal regional disparities, with concentration in CALABARZON, Central Luzon, and NCR, while underserved areas, particularly in Mindanao, face persistent barriers. Analysis of compliance rates shows that 69% of SUCs have achieved a Certificate of Program Compliance (COPC), though postgraduate programs lag behind undergraduate offerings. Teacher Education Programs' performance in licensure exams further underscores disparities between main and satellite campuses. The study concludes that optimizing existing SUC campuses through improved resource allocation, targeted policies, and sustainable funding solutions can enhance educational outcomes, support local and regional development, and create a more inclusive higher education system in the Philippines.
Keywords: 330; State Universities and Colleges; satellite campuses; cost-effectiveness analysis; cost considerations of establishing satellite campuses; cost considerations of supporting learners